Oral Hygiene Instructions and Shortcomings in Child Laborers: Oral hygiene and child laborers - Atarbashi-Moghadam, Fazele; Heydary, Maryam; Madihi, Saeed (Journal of Dental School, 2023)
Objectives Child labor is an important phenomenon affecting global health. However, studies concerning the oral and dental health of child laborers are limited. The present study aimed to assess the effectiveness of oral hygiene instructions in a group of child laborers under the protection of a charity. Method In this cross-sectional interventional study, the sociodemographic information and the Oral Hygiene Index-Simplified (OHI-S) scores of a group of working children were collected. Oral hygiene tools were provided for the children, and proper instructions were given to them. After three months, the plaque index and the reasons for its non-reduction were gathered. Descriptive indices were calculated for data presentation. Results A total of 79 child laborers (mean age, 11.8±1.29 years), including 30 females and 49 males, were evaluated in this study. Based on the results, 51 (64.6%) children had used a toothbrush at least once before the study. Three months after giving the oral health instructions and providing the oral hygiene tools, 12 children were removed from the study due to a lack of follow-up. Of the remaining 67 children, 34 had brushed their teeth at least once (64.7%) or twice (35.2%) a day. The OHI-S score reduction was statistically significant (P=0.013). Conclusion According to the results, instructing working children on oral health and providing them with proper oral hygiene tools, such as toothbrush, toothpaste, and dental floss, could be effective in improving their oral health and could enhance their cooperation significantly.